2022
DOI: 10.1007/s11695-021-05881-1
|View full text |Cite
|
Sign up to set email alerts
|

Management of a Late-Term Hiatal Hernia with Intrathoracic Pouch Migration After Roux-en-Y Gastric Bypass

Abstract: Publisher's Note Springer Nature remains neutral with regard to jurisdictional claims in published maps and institutional affiliations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…ITSM with HH is a well-known cause of GERD, dysphagia and epigastric pain after MBS but has a high rate of missed diagnoses because the presenting complaints are assumed to be simple post-MBS GERD which is often managed conservatively. 41 In a report by Saba et al, 42 the incidence of ITSM has been reported to be up to 72.5% after MBS. Potential mechanisms for recurrent ITSM include excessive manipulation of the diaphragmatic crura, a surgical section of anchoring phrenogastric and phrenoesophageal ligaments, dissection of the angle of His, and loss of the hiatal fat pad secondary to rapid weight loss.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…ITSM with HH is a well-known cause of GERD, dysphagia and epigastric pain after MBS but has a high rate of missed diagnoses because the presenting complaints are assumed to be simple post-MBS GERD which is often managed conservatively. 41 In a report by Saba et al, 42 the incidence of ITSM has been reported to be up to 72.5% after MBS. Potential mechanisms for recurrent ITSM include excessive manipulation of the diaphragmatic crura, a surgical section of anchoring phrenogastric and phrenoesophageal ligaments, dissection of the angle of His, and loss of the hiatal fat pad secondary to rapid weight loss.…”
Section: Discussionmentioning
confidence: 97%
“…Our meta-analysis revealed a low incidence of gastric sleeve migration after LTA. ITSM with HH is a well-known cause of GERD, dysphagia and epigastric pain after MBS but has a high rate of missed diagnoses because the presenting complaints are assumed to be simple post-MBS GERD which is often managed conservatively 41 . In a report by Saba et al, 42 the incidence of ITSM has been reported to be up to 72.5% after MBS.…”
Section: Discussionmentioning
confidence: 99%
“…The management of surgical emergencies during pregnancy following MBS is another topic of interest, which is predicted to increase over the following years, owing to the increase in metabolic bariatric operations worldwide [ 54 , 55 ], the improvement of female fertility following MBS [ 56 , 57 ], and the reduction of visceral fat that may serve as a predisposing mechanism for the formation of internal hernias [ 58 , 59 ]. Typically, the acute abdomen after MBS is treated laparoscopically; however, special considerations that apply to pregnancy should be addressed effectively before deciding the surgical access [ 60 ].…”
Section: Reviewmentioning
confidence: 99%
“…The evidence on HH post-RYGB is based on case reports and case series, among which the largest one includes 7 patients [87][88][89][90]. In this context, HH constitutes a late complication, with patients presenting 2-14 years following the index RYGB procedure.…”
Section: Hiatal Hernia After Roux-en-y Gastric Bypassmentioning
confidence: 99%
“…In this context, HH constitutes a late complication, with patients presenting 2-14 years following the index RYGB procedure. Several mechanisms have been proposed to contribute to this condition, including rapid weight loss after MBS which is associated with relaxation of the phrenoesophageal ligament of Laimer and widening of the hiatus, creation of a large pouch with an ensuing higher intragastric pressure, extended dissection of the cardia and the left crus, or a small pre-existing hernia that enlarges over time [90][91][92]…”
Section: Hiatal Hernia After Roux-en-y Gastric Bypassmentioning
confidence: 99%